Labor market policies, unemployment, and identity - Ronnie Schöb (IZA World of Labor, 2021)
Unemployment not only causes material hardship but can also affect an individual's sense of identity (i.e. their perception of belonging to a specific social group) and, consequently, feelings of personal happiness and subjective well-being. Labor market policies designed to help the unemployed may not overcome their misery: wage subsidies can be stigmatizing, measures that require some work or attendance for training from those receiving benefits (workfare) may not provide the intended incentives, and a combination of an unregulated labor market and policy measures that bring people who became unemployed quickly back to work (flexicurity) may increase uncertainty. Policies aimed at bringing people back to work should thus take the subjective well-being of the affected persons more into consideration.
Keywords: I31; I38; J60; D60; 330; unemployment; identity; well-being; wage subsidies; income support; workfare